Analisis Persebaran Toko Parfum di Lowokwaru Malang Menggunakan QGIS untuk Optimalisasi Lokasi Bisnis - Nasrullah, Ardra Fajar; Wahyuni, Ida (Fakultas Ilmu Komputer, Universitas Jember, 2025)
This service aims to produce a thematic map that describes the distribution of shops or perfume sales outlets in Lowokwaru District, Malang. This sub-district has high economic activity and is one of the strategic areas in Malang City. Capable spatial data is needed to analyze distribution patterns and support business decision making. This service uses a field survey method to collect primary data, which is then processed using QGIS software. The data collected includes the location of the perfume shop, regional characteristics and accessibility. Furthermore, spatial analysis was carried out to identify the concentration pattern of perfume outlets in the area. The results of its service show that perfume outlets shine in areas with high accessibility, such as around campuses, shopping centers and areas with dense commercial activity. On the other hand, several other areas, such as organizational and peripheral areas, have market potential that has not been exploited optimally. This shows an opportunity for business actors to develop more effective marketing strategies and reach underserved areas.